Hydroformylation of vegetable oils and the potential use of hydroformylated fatty acids. Issue 9 (4th September 2013) - Lee Chang, Kim Jye; Nichols, Peter D.; Blackburn, Susan I.
Abstract Cultivation of microalgae has potential in producing a feedstock for biofuels and, in addition, high‐value lipid bioproducts such as long‐chain (⪈C20, LC) omega‐3 oils, carotenoid pigments and squalene, as well as other non‐lipid materials including exopolysaccharide. The high‐value LC omega‐3 oils have been conventionally sourced from fish. This paper provides a perspective on our recent study of the heterotrophic growth of thraustochytrids for their wider biotechnological potential, including as a source of a range of higher value lipids in addition to biofuels.